5-Methyl-2-phenyl-2H-pyrazol-3-ol - Feng Zhi; Yi-Lin Yang; Rong Wang; Yi Zhang; Qiang Wang (Acta Crystallographica Section E, 2008)
The title compound, C10H10N2O, known as Edaravone (MCI-186), was crystallized from methanol. The two independent molecules in the asymmetric unit are linked through an O—H...O hydrogen bond. One molecule adopts a ketone form, while the other adopts an enol form. In the crystal structure, molecules are linked through intermolecular N—H...O hydrogen bonds, forming chains running along the b axis.